Inflammatory Cytokines Shape an Altered Immune Response During Myeloid Malignancies - Camacho, Virginia; Kuznetsova, Valeriya; Welner, Robert S. (Frontiers in Immunology, 2021)
The immune microenvironment is a critical driver and regulator of leukemic progression and hematological disease. Recent investigations have demonstrated that multiple immune components play a central role in regulating hematopoiesis, and dysfunction at the immune cell level significantly contributes to neoplastic disease. Immune cells are acutely sensitive to remodeling by leukemic inflammatory cytokine exposure. Importantly, immune cells are the principal cytokine producers in the hematopoietic system, representing an untapped frontier for clinical interventions. Due to a proinflammatory cytokine environment, dysregulation of immune cell states is a hallmark of hematological disease and neoplasia. Malignant immune adaptations have profound effects on leukemic blast proliferation, disease propagation, and drug-resistance. Conversely, targeting the immune landscape to restore hematopoietic function and limit leukemic expansion may have significant therapeutic value. Despite the fundamental role of the immune microenvironment during the initiation, progression, and treatment response of hematological disease, a detailed examination of how leukemic cytokines alter immune cells to permit, promote, or inhibit leukemia growth is lacking. Here we outline an immune-based model of leukemic transformation and highlight how the profound effect of immune alterations on the trajectory of malignancy. The focus of this review is to summarize current knowledge about the impacts of pro- and anti-inflammatory cytokines on immune cells subsets, their modes of action, and immunotherapeutic approaches with the potential to improve clinical outcomes for patients suffering from hematological myeloid malignancies.